Jakarta’s urban culture representation on social media @jakarta_tourism: A semiotics analysis - Marco Triary Hardy; Daniel Susilo (Universitas Trunojoyo Madura, 2022)
Social media can form the identity of the representation content. The content of the Instagram account @jakarta_tourism represents the identity of the urban culture of Jakarta as a tourism brand. This study aims to find out and reveal the representation of Jakarta as a city of urban culture, based on the signs from the content of the Instagram account @jakarta_tourism. This study is descriptive qualitative using the constructivist paradigm using the semiotic analysis method by Roland Barthes. The main focus of the semiotic analysis by Roland Barthes is to find the meaning of denotation, connotation, and myth of a sign. The results in this study indicate that some content of the Instagram account @jakarta_tourism represents Jakarta as a city of urban culture and highlight that as part of the brand of Jakarta Tourism. That was revealed after this research analyzed using syntagmatic and paradigmatic studies on posts of Instagram account @jakarta_tourism to find the meaning of denotation and connotation/ myth. As for the myth, it is shown that the concept of urban culture is closely related to acculturation forms of urban culture and urban society and space to express various arts and cultures.